Deteksi Boraks Pada Bakso Di Kota Kupang Dengan Menggunakan Rapid Test Kit Boraks - Ati, Winarti Delfiana; Sulmiyati, Sulmiyati; Armadianto, Heri; Sipahelut, Geertruida M. (Yayasan Sumber Daya Manusia Cerdas, 2024)
Borax is a chemical substance that is not included as a food additive but is used several times in making meatballs. This study aims, 1) to compare the results of meatballs detected using borax rapid test kit, organoleptic test, and confirmation test, borax pH test, 2) to determine the use of borax in meatball traders scattered in Kupang city. This research was conducted at the Laboratory of Animal Product Technology of Undana Animal Husbandry. The research method used is a survey method. The observed variables were borax detection with borax rapid test kit, organoleptic test, confirmation test, and pH test. The results showed the results of laboratory tests on 25 samples of meatballs taken from traders in Kupang city using the borax rapid test kit, there were 5 samples of meatballs detected borax from the results of the borax rapid test kit test, the results of the organoleptic test showed that color, aroma, texture, there was no difference between meatballs detected borax while there was a difference in taste (P>0.05), the affirmation test showed that there was no difference between detected and undetected meatballs, and the pH test showed that there was no difference between those detected borax and those not detected borax. Based on the results of the discussion, it can be concluded that the laboratory test results of 25 meatball samples taken from traders.